2018
DOI: 10.4274/tjh.2018.0221
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Relationship Between Fok1 and Col1A1 Gene Polymorphisms and Development of Treatment-Related Bone Complications in Children with Acute Lymphoblastic Leukemia

Abstract: In acute lymphoblastic leukemia (ALL), various clinical risk factors and genetic predispositions contribute to the development of bone complications during and after chemotherapy. In this study, we aimed to investigate whether vitamin D receptor (VDR) Fok1 and collagen protein Col1A1 Sp1-binding site gene polymorphisms, which are important in bone mineral and matrix formation, have effects on the development of bone abnormalities in childhood ALL survivors. Materials and Methods: Fifty children with ALL who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…Donmez, et al [13] found osteopenia in 23.1% and osteoporosis in 7.7% of patients in their survey. In another study from Turkey, reported low BMD in 32%, osteoporosis in 24% and osteonecrosis in 16% of patients [14]. We found low BMD in 50% and osteoporosis in 12% of patients in our study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Donmez, et al [13] found osteopenia in 23.1% and osteoporosis in 7.7% of patients in their survey. In another study from Turkey, reported low BMD in 32%, osteoporosis in 24% and osteonecrosis in 16% of patients [14]. We found low BMD in 50% and osteoporosis in 12% of patients in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Vitanza, et al [15] found that the overall difference in BMD after six years from cessation of chemotherapy among three age groups patients defined as ages under five years group 1, ages five to 10 years group 2 and ages above 10 years at the time of diagnosis, significant difference was found between group 1 and group 3. Similar to Vitanza, et al [15] study, Erdem, et al [14] found that the rate of osteonecrosis and bone changes were significantly higher in patients aged above 10 years. As summarized above, varying results were obtained on factors affecting to BMD in different studies.…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that collagen types II and V are associated with non‐traumatic ONFH, but few studies have investigated the relationship between type I collagen and osteonecrosis. Recently, a prospective study involving 50 children with acute lymphoblastic leukemia who received GC therapy showed a significant association between collagen protein Col1A1 Sp1‐binding site gene polymorphisms and development of osteonecrosis in a long‐term follow‐up . Although osteonecrosis affected different areas, including the femoral head in two patients, and the sacroiliac joints and lumbar spine in one patient each, the study provided preliminary but compelling evidence for a possible correlation between type I collagen and osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the vitamin D receptor (VDR) Fok1, as well as the collagen protein Col1A1 Sp1-binding site gene polymorphisms, which play a role in bone mineral and matrix formation, were previously investigated for their role in bone complications due to therapy in 50 pediatric patients with ALL, who were treated with the ALL Berlin-Frankfurt-Muenster-95 protocol between 1998 and 2008. A higher risk of therapy-induced bone mineral loss and osteonecrosis was found in patients aged ≥10 years and with vitamin D deficiency (56).…”
Section: Daunorubicin (Dnr)mentioning
confidence: 95%